Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook. (30th June 2023) - Cui, Ma-Lin; Lin, Zi-Xuan; Xie, Qing-Fan; Zhang, Xiao-Yan; Wang, Bing-Qing; Huang, Miao-Ling; Yang, Da-Peng
Highlights: The luminescence and aptamer based TCs determination methods were discussed. The removal, and degradation of TCs residues were reviewed. The advantages and limitations of these strategies were analyzed and discussed. The mechanisms of sensing, adsorption and degradation were summarizing. The outlook and potential challenges of TCs residues degradation were suggested. Abstract: Tetracycline antibiotics (TCs), one of the important antibiotic groups, have been widely used in human and veterinary medicines. Their residues in foodstuff, soil and sewage have caused serious threats to food safety, ecological environment and human health. Here, we reviewed the potential harms of TCs residues to foodstuff, environment and human beings, discussed the luminescence and aptamer sensors based analytical determination, adsorptive removal, and degradation strategies of TCs residues from a recent 5-year period. The advantages and intrinsic limitations of these strategies have been compared and discussed, the potential challenges and opportunities in TCs residues degradation have also been deliberated and explored.